Peripheral Spexin Inhibited Food Intake in Mice - Shuangyu Lv; Yuchen Zhou; Yu Feng; Xiaomei Zhang; Xinyue Wang; Yanjie Yang; Xinchun Wang (International Journal of Endocrinology)
Spexin (SPX, NPQ), a novel endogenous neuropeptide, was firstly identified by bioinformatics. Spexin gene and protein widely distributed in the central nervous system and peripheral tissues, such as the hypothalamus and digestive tract. The role of spexin in appetite regulation in mammalian is still unclear. The present study was designed to investigate the mechanism and effect of peripheral spexin on food intake in mice. During the light period, an intraperitoneal (i.p.) injection of spexin (10 nmol/mouse) significantly inhibited cumulative food intake at 2, 4, and 6 h after treatment in fasted mice. During the dark period, spexin (1 and 10 nmol/mouse, i.p.) significantly suppressed cumulative food intake at 4 and 6 h after treatment in freely feeding mice. The GALR3 antagonist SNAP37889, not GALR2 antagonist, significantly antagonized the inhibitory effect on cumulative food intake (0–6 h) induced by spexin. Spexin significantly reduced the mRNA level of Npy mRNA, not Agrp, Pomc, Cart, Crh, Orexin, or Mch, in the hypothalamus. Spexin (10 nmol/mouse, i.p.) increased the number of c-Fos positive neurons in hypothalamic AHA and SCN, but not in ARC, DMN, LHA, PVN, SON, or VMH. The hypothalamic p-CaMK2 protein expression was upregulated by spexin. This study indicated that acute peripheral injection of spexin inhibited mouse food intake. The anorectic effect may be mediated by GALR3, and inhibiting neuropeptide Y (NPY) via p-CaMK2 and c-Fos in the hypothalamus.